1999
DOI: 10.1086/520135
|View full text |Cite
|
Sign up to set email alerts
|

Cure of Implantable Venous Port–Associated Bloodstream Infections in Pediatric Hematology‐Oncology Patients without Catheter Removal

Abstract: The efficacy of antibiotic treatment of port-associated bloodstream infection without device removal has not been systematically studied. We analyzed the outcome of 43 consecutive portassociated bloodstream infections in pediatric hematology-oncology patients. Etiologies included Staphylococcus epidermidis (30) and Staphylococcus aureus (6). Antibiotics were given through the port for a median of 11 days. Four ports were removed within 72 hours. In 36 (92%) of the remaining 39 episodes, there was a response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 19 publications
(11 reference statements)
4
23
0
3
Order By: Relevance
“…As reported previously, 12,20,22,25,26 coagulase-negative staphylococcus was the dominant organism in implantable ports. It is possible that skin flora grow down the outside of the needle, leading to colonization and infection.…”
Section: Discussionsupporting
confidence: 70%
“…As reported previously, 12,20,22,25,26 coagulase-negative staphylococcus was the dominant organism in implantable ports. It is possible that skin flora grow down the outside of the needle, leading to colonization and infection.…”
Section: Discussionsupporting
confidence: 70%
“…CRB is known to be frequently caused by CNS, a microorganism known for its low pathogenicity and its high probability of cure without IVD removal (3) but is less often described when caused by pathogenic microorganisms (26). Therefore, it seems extremely difficult to draw any conclusions about episodes affecting patients with neutropenia and/or another infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several cancer centers have shown that CRB occurs in 10 to 20% of hospitalized patients with cancer (13,16,17). In cancer patients, it is preferable not to remove the IVD if the microorganism species allows it to be left in place, and several authors showed the efficacy of antibiotic treatment of portassociated bacteremia without IVD removal (26).…”
mentioning
confidence: 99%
“…The results of a number of studies of children have suggested that some catheter-related infections may be cleared by antimicrobial therapy alone, and that the CVC need not be removed in up to 75% of cases [67,68,69,70,71,72,73]. Furthermore, although there have been anecdotal reports of the cure of fungemia without catheter removal, the treatment of CVC-associated fungemia while retaining the catheter has a low success rate and may be associated with a higher mortality [8].…”
Section: Catheter Replacementmentioning
confidence: 99%